Time for gift giving: Abnormal share repurchase returns and uncertainty - Anolick, Nina; Batten, Jonathan A.; Kinateder, Harald; Wagner, Niklas (Journal of Corporate Finance, 2021)
We study share repurchase announcements for nine European countries between 2000 and 2017. In contrast to previous studies, we address the role of market uncertainty as a market-based determinant of positive average abnormal announcement returns, while including governance, liquidity risk and firm related control variables. Economic policy uncertainty and financial uncertainty, individually as well as jointly, positively affect abnormal returns. We suggest that this relation is due to a stronger signaling effect under increased uncertainty, as both information asymmetry and underpricing tend to increase. Also, a potential hedge against adverse market movements is more valuable. Optimal timing of repurchase announcements should therefore consider market uncertainty conditions.